Intra- and inter-regional expansion: a nonlinear model. Issue 7 (8th July 2019) - Zhang, Hua; Qian, Gongming; Li, Lee; Qian, Zhengming
Abstract : Purpose: The purpose of this paper is to differentiate between intra- and inter-regional diversification and explore how each affects firm performance. Existing studies show that both intra- and inter-regional expansion provide benefits and incur costs but the findings are mixed. This study aims to explain the mixed findings. Design/methodology/approach: This study uses secondary data and quantitative methodologies to test hypotheses. Findings: Using data from 663 Canadian firms over a six-year period (2006–2011), the authors find that the relationship between firm performance and the depth and width of intra-regional expansion is nonlinear. The authors also find a sigmoid-shaped relationship between firm performance and inter-regional diversification, i.e., performance initially increases with home regional diversification, decreases with bi-regional diversification and finally increases again with multi-regional diversification. Originality/value: The findings of this study shed light on the current debate on the merits of inter- and intra-regional diversification and have important theoretical and managerial implications.